Anti-Inflammatory and oral toxicity assessment Of R-38TM: a traditional herbal supplement for arthritis - Mohamad, Anis Amirah; Abdul Majid, Fadzilah Adibah; Assaw, Suvic; Zainal Abidin, Fadhilah; Fadhlina, Anis; Aluru, Sudheer Kumar; Zainol, Siti Nurazwa; Ahmed, Najat Jabbar (UTM Press, 2021)
R-38TM is a traditional herbal supplement for treating arthritis-related conditions. High-performance liquid chromatography (HPLC) analysis was performed for identification and quantification of rosmarinic acid in the R-38TM water extract. The anti-arthritic potential of the R-38TM water extract was investigated by measuring the production of IL-6 and TNF-α in inflamed cells. Xanthine oxidase (XO) and cyclooxygenase-2 (COX-2) inhibition assays were also conducted. The cytotoxic effect of R-38TM water extract was investigated on HSF1184 cell line. Acute and subacute oral toxicity studies were conducted on female SpragueDawley (SD) rats. The rosmarinic acid was identified at 1.208 min (3.61 %w/w). The inflamed cells showed a decrease in the production of IL-6 (55.9%) and TNF-α (52.13%). The COX-2 and XO enzymes were moderately inhibited by R-38TM water extract. The cytotoxicity analysis showed no cytotoxic effect on the cell. The acute and subacute oral toxicity studies revealed no mortality and normal body weight at all doses. There were no significant differences (p > 0.05) in organ weight, hematological and biochemical parameters, and histology of liver and kidneys with the control group. In conclusion, R-38TM water extract exhibited no toxic effect orally and may possess potential therapeutic properties against pro-inflammatory diseases including arthritis.